DEVELOPMENT OF SPECIAL STRENGTH OF 15-16-YEAR-OLD BOXERS THROUGH ACTION GAMES - Shodibek Murotov (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about active games that help the bodies and minds of 15-16-year-old children, who are tired of training, to relax, and their types, importance, results of application, and the results that can be achieved. In addition, the tasks and roles of the trainer and participants in the implementation of action games are explained based on the relevant games.